Erosive Arthritis, Fibromatosis, and Keloids: A Rare Dermatoarthropathy - Fawad Aslam; Jonathan A. Flug; Yousif Yonan; Shelley S. Noland (Case Reports in Rheumatology)
Polyfibromatosis is a rare disease characterized by fibrosis manifesting in different locations. It is commonly characterized by palmar fibromatosis (Dupuytren’s contracture) in variable combinations with plantar fibromatosis (Ledderhose’s disease), penile fibromatosis (Peyronie’s disease), knuckle pads, and keloids. There are only three reported cases of polyfibromatosis and keloids with erosive arthritis. We report one such case and review the existing literature on this rare syndrome.